Looking like the Father: The Meaning of Life and the Transfigured Gaze - Rumpza, Stephanie (Filozofia Chrześcijańska, 2022)
In this nihilistic age, the worth of life is often measured by utility. This paper challenges such an approach by turning attention away from what is given to focus on how we receive it. Drawing inspiration from the theological tradition of the icon, I discuss how we can understand this shift as a “transfiguration of vision.” A close study of the act of prayer before the icon reveals how we can gain distinct manner of seeing, which in turn has implications for the way we understand life.